The Roles of Embryonic Transcription Factor BRACHYURY in Tumorigenesis and Progression - Chen, Ming; Wu, Yinghui; Zhang, Hong; Li, Suoyuan; Zhou, Jundong; Shen, Jun (Frontiers in Oncology, 2020)
Transcription factor brachyury, with a DNA-binding T-domain, regulates posterior mesoderm formation and notochord development through binding with highly conserved palindromic consensus sequence in a variety of organisms. The absence of brachyury expression in majority of adult normal tissues and exclusive tumor-specific expression provides the potential to be developed into a novel and promising diagnostic and therapeutic target in cancer. As a sensitive and specific marker in the diagnosis of chordoma, brachyury protein has been verified to involve in the process of carcinogenesis and progression of chordoma and several epithelial carcinomas in various studies, but the mechanism by which brachyury promotes tumor cells migrate, invade and metastasis still remains less clear. To this end, we attempt to summarize the literature on the upstream regulatory pathway of brachyury transcription and downstream controlling network by brachyury activation, all of which involve in both the embryonic development and tumor progression. We present the respective correlation of brachyury expression with tumor progression, distant metastasis, survival rate and prognosis in several types of tumor samples (including chordoma, lung cancer, breast carcinoma, and prostate cancer), and various brachyury gain-of-function and loss-of-function experiments are summarized to explore its specific role in respective tumor cell line in vitro. In addition, we also discuss another two programs relating to brachyury function: epithelial-to-mesenchymal transition (EMT) and cell cycle control, both of which implicate in the regulation of brachyury on biological behavior of tumor cells. This review will provide an overview of the function of master transcriptional factor brachyury, compare the similarities and differences of its role between embryonic development and carcinogenesis, and list the evidence on which brachyury-target therapies have the potential to help control advanced cancer populations.